A password-authenticated secure channel for App to Java Card applet communication. Issue 4 (2nd November 2015) - Hölzl, Michael; Asnake, Endalkachew; Mayrhofer, Rene; Roland, Michael
Abstract : Purpose: – The purpose of this paper is to design, implement and evaluate the usage of the password-authenticated secure channel protocol SRP to protect the communication of a mobile application to a Java Card applet. The usage of security and privacy sensitive systems on mobile devices, such as mobile banking, mobile credit cards, mobile ticketing or mobile digital identities has continuously risen in recent years. This development makes the protection of personal and security sensitive data on mobile devices more important than ever. Design/methodology/approach: – A common approach for the protection of sensitive data is to use additional hardware such as smart cards or secure elements. The communication between such dedicated hardware and back-end management systems uses strong cryptography. However, the data transfer between applications on the mobile device and so-called applets on the dedicated hardware is often either unencrypted (and interceptable by malicious software) or encrypted with static keys stored in applications. Findings: – To address this issue, this paper presents a solution for fine-grained secure application-to-applet communication based on Secure Remote Password (SRP-6a and SRP-5), an authenticated key agreement protocol, with a user-provided password at run-time. Originality/value: – By exploiting the Java Card cryptographic application programming interfaces (APIs) and minor adaptations to the protocol, which do not affect the security, the authors were able to implement this scheme on Java Cards with reasonable computation time.